Computer program for the choice of therapeutic approaches to the treatment of gastroduodenal ulcer bleeding in patients with coronary heart disease - A. M. Khadjibayev; R. I. Rakhimov; A. G. Makhamadaminov; A. B. Yeshmuratov (Сибирский научный медицинский журнал, 2021)
The developed computer program for choosing the tactics of treating patients with gastro duodenal ulcerous bleeding (GDUB) combined with various forms of coronary heart disease to the fullest extent meets demands not only practical emergency medicine, but modern evidence-based medicine. The presented case of clinical observation serves the clear illustration of this issue, which convincingly indicates that use of the developed computer program to choose the tactics of treating patients with GDUB combined with various forms of coronary heart disease allows us not only to accurately establish the clinical diagnosis, but also to choose the most appropriate treatment tactic.